Hypno-NLP in Hindu Theological Education: Institutional Rationale, Cultural Adaptation, and Stakeholder Perceptions in Bali - Suandewa, I Gusti Lanang Agung; Ananda, I Nyoman; Wiguna, I Made Arsa (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
Little is known about how scientifically contested psychological approaches are incorporated into Hindu theological education. This study examines the institutional rationale for integrating Hypno-Neuro-Linguistic Programming (Hypno-NLP) into the Level 1 Hindu Theology Course at Pinandita Sanggraha Nusantara, Bali Regional Coordinating Unit (PSN Korwil Bali), its instructional and cultural adaptation, and stakeholders’ perceptions of its implications for religious authority, communication, and the internalization of Hindu values. A qualitative single-case study was conducted using semi-structured interviews with eight informants: one institutional leader, one instructor, four participants serving as Pamangku (Balinese Hindu ritual officiants), and two recipients of their religious services. The data also included four audiovisual course recordings totaling approximately seven hours and forty minutes and relevant institutional documents. The materials were analyzed thematically by comparing institutional, instructional, participant, community, observational, and documentary sources. The institution introduced Hypno-NLP to complement theological and ritual instruction with communication-oriented material. The course combined conceptual explanation, pre-talk, demonstrations, exercises, discussion, and reflection, adapted through Indonesian and Balinese, respectful forms of address, and examples from Hindu ritual contexts. Participants perceived selected elements as relevant to calmness, confidence, communicative flexibility, and interaction with devotees, while two service recipients positively described preliminary dialogue, ritual explanation, and religious advice. Religious communication was the most consistently perceived area of relevance; evidence concerning religious authority and value internalization remained limited and subjective. The findings do not establish causal, clinical, spiritual, or community-wide effects. They support a cautious distinction between generally applicable communication practices and contested claims concerning NLP, anchoring, and subconscious programming.